A Comparative Study of Introductory and Undergraduate Econometric Textbooks - Harris, Mark; MacQuarie, L. (Wiley-Blackwell, 1995)
There are currently numerous introductory and undergraduate econometric textbooks. This is unfortunate for both the new student of econometrics wishing to purchase a textbook, and for course conveners who have the responsibility of recommending a text. There is a shortfall in the literature reviewing such textbooks and thus providing assistance for the appropriate choice of textbook. This paper is an attempt to fill this gap, by comprehensively reviewing some of the mainstream undergraduate econometric textbooks.